Re‐valuation of annual cytology using HPV self‐sampling to upgrade prevention (REACH UP): A feasibility study in women living with HIV in the UK. Issue 4 (3rd March 2022) - Cicconi, Paola; Wells, Charlotte; McCarthy, Blanka; Wareing, Susan; Andersson, Monique Ingrid; Fox, Julie; Lwanga, Julianne; Pal, Nisha; Burns, Fiona; Woodward, Clare; Malek, Ramona; Sabin, Caroline Anne; et al.
Abstract: Introduction: Current UK guidelines for cervical cancer screening are based on the assumption that most women living with HIV (WLWH) are also high‐risk (HR) human papillomavirus (HPV)‐positive. We aimed to provide data on prevalence of HR‐HPV in WLWH in the UK and to assess feasibility and acceptability of HR‐HPV self‐sampling in this group. Methods: Women living with HIV attending six HIV services in London/south of England, with no history of cervical cancer, were enrolled. Participants self‐collected a vaginal swab for the detection of HR‐HPV, completed a survey about sexual/gynaecological history, attitudes towards annual screening and perception of HR‐HPV self‐sampling, and were asked to have their annual cervical smear. Results: In all, 67 women were included: 86.5% were of black ethnicity, the median (range) age was 47 (24–60) years, median CD4 T‐cell count was 683 cells/µL [interquartile range (IQR): 527–910], and 95.4% had viral load ≤ 50 copies/mL. All performed the vaginal swab. Eighteen (27%) had no cervical smear results; none of these women attended HIV services where this was routinely offered. No cervical samples were positive for HR‐HPV. Three‐quarters (75.8%) of participants reported adherence to annual screening, with only one woman (1.5%) attending irregularly. On visual analogue scales (from 0 to 100), median (IQR) acceptability and necessity of smear tests were 100 (75–100) and 100 (85–100), respectively. Conclusions: Our results suggest that the prevalence of HR‐HPV in WLWH in the UK may be low. Self‐sampling seems to be acceptable, suggesting, if validated, its potential role in supporting less frequent smear testing and improving screening uptake in WLWH.